Psychometric Properties of Beck Depression Inventory-II for High School Children in Shiraz City, Iran - Faranak Toosi; Changiz Rahimi; Samad Sajjadi (Shiraz University of Medical Sciences, 2017)
Background: Depression causes poor academic performance, substance abuse, antisocial behavior, school avoidance, and running away from home in adolescents. Due to the high prevalence of depression in adolescents, reliability, and validity of this questionnaire in this age group is of special importance. Symptoms of depression in children and adolescents are different from their indications in adults. Objectives: The current study aimed at assessing reliability and validity of the Beck depression inventory- second edition (BDI- II) in high school students in Shiraz, Iran. Methods: A total of 1150 high school students from Shiraz were selected to assess the validity and a sum of 128 students from the same city were tested to measure the reliability of the study. Concurrent validity and factor analysis were used to assess validity. Concurrent validity was assessed using Beck anxiety inventory and depression anxiety stress scale (DASS)-21. Factor analysis was computed using varimax rotation method. To assess reliability, test-retest and Cronbach's alpha were adopted. Results: Correlation coefficients for the concurrent validity of this inventory with Beck anxiety inventory and DASS-21 were 0.45 and 0.55, respectively. The results of factor analysis with varimax rotation method showed 4 factors that predicted 43.69% of the total variance of the test. The reliability and correlation coefficients 0.55 and 0.83 were obtained from test-retest and Cronbach's alpha methods, respectively. Conclusions: Based on the results of the current study, researchers can use BDI- II in psychological research and clinical use for high school students in Shiraz.